(untitled) (Proceedings of the International Conference on Public Health, 2017)
The purpose of this qualitative study aimed to study learning of youth through the community volunteering spirit process in a socio-cultural context. The study was conducted in one municipality located in Sra-kaew province from December 2015 to October 2016. This study employed critical ethnography method as the research design and it was divided into 3 phases: 1) exploring the community to understand socio-cultural context, 2) studying the situation or event contributing youth volunteering spirit, and characteristic of youth volunteer in a community and 3) analyzing the outcome or learning of youth from the development of volunteerism system in youths by community.The participants were divided into 2 groups, including 42 key informants and 19 general informants. The data were collected using participant observation, in-depth interviews and focus group discussions, and analyzed by content analysis. The results indicated as follows. 1) The incidents and event causing youth volunteerism; Problems and needs in the community, National and local policies, Cultural practice, Cultural activities. 2) Five characteristics of the volunteering work of the youth; Sociological, Economical, Environmental, Health-related and Political characteristics 3) Seven Outcome from volunteer worked